Loneliness and depression among men in Poland: cross-sectional study - Dziedzic, Beata; Kobos, Ewa; Przylepa, Katarzyna; Idzik, Anna (Frontiers in Public Health, 2025)
IntroductionMental well-being is defined as subjective feeling characterized by an emotional and cognitive evaluation of one’s life that may could lead to high life satisfaction and low levels of negative emotions. Research findings confirm that individuals with an elevated level of loneliness often face mental health issues. Loneliness is recognize as an important potential predictor of depressive symptoms, anxiety, and suicidal thoughts. As mental health concerns are a serious crisis in many countries around the world, it is important to conduct research aimed at identifying those affected by this problem. Due to the reluctance of some men to seek professional health care, there is a need for screening tests to assess the risk of anxiety, depression and level of loneliness in this gender. The aim of the study was to assess the prevalence of anxiety symptoms, depression, irritability and assess the level of loneliness among men.MethodsThe study was conducted on a representative sample of 438 men who completed a survey through an online portal using the Computer-Assisted Web Interviewing (CAWI) technique. The Hospital Anxiety and Depression Scale (HADS-M) and the UCLA Loneliness Scale (R-UCLA) were used to assess mental well-being. These scales assess only some aspects of mental well-being and are used in screening tests. The average age of the participating men was 45.61 ± 15.64 years.ResultsOn the HADS-M scale, participants scored an average of 13.91 ± 9.35 points. Anxiety clinically relevant symptoms were identified in 21.91% of the participants on the anxiety subscale, and depressive clinically relevant symptoms in 12.55% on the depression subscale. On the loneliness scale, participants scored an average of 40.50 ± 10.78 points, indicating moderate level of loneliness. A moderately high and very elevated level of loneliness was found in 21.00 and 2.30% of the participants, respectively.ConclusionIn this study, one fifth of the participants experienced anxiety clinically relevant symptoms, and every tenth man demonstrated depressive clinically relevant symptoms. Every fifth man experienced a moderately elevated level of loneliness. The main potential predictor of depression symptoms and higher levels of loneliness was the poor financial situation of the participants and a lack of financial decisiveness.